Neonatal respiratory depression associated with epidural analgesia - Alberto Gálvez Toro; Antonio Muñoz Martínez; Susana Sánchez Moreno (Fundación para el Desarrollo de la Enfermería, 2013)
Background: Epidural analgesia is the most effective analgesics used during childbirth but is not without its problems.In the Hospital San Juan de la Cruz of Ubeda from November 2011 we have detected 3 cases of newborn infants with signs of respiratory depression. Appeared in them: normal cardiotocographic records during childbirth, use of epidural associated with fentanyl, termination by vacuum and elevated temperature in one case.ObjectivesKnow if the neonatal adaptation to extrauterine life may be influenced by the use of epidural analgesia in childbirth. Review what role can have the rise in maternal temperature and the use of epidural fentanyl with the appearance of newborn respiratory distress.MethodsLiterature Review conducted in February of 2012 in Pubmed and the Cochrane Library, using the key words: childbirth, epidural analgesia, neonatal respiratory depression.ResultsOn the respiratory depression associated with fentanyl, a Cochrane review found indicating that newborns of mothers with an epidural, had a lower pH and were less need for administration of naloxone.On PubMed we find a review study that indicates that the respiratory depression caused by the administration of opioids via neuroaxial is rare, placing it below 1 per 1000, and a clinical case that concluded that doses of fentanyl exceeding 300 µg (approx. 5 µg/kg) for 4 hours previous to childbirth, have a high risk of neonatal respiratory depression at birth.The same Cochrane review indicates that the women with epidural analgesia had increased risk of maternal fever of at least 38 ° C and a recent cohort study relates this increase in temperature with a greater likelihood of neonatal adverse events (from 37.5 ° C).ConclusionsThe studies found considered safe epidurals to the neonate and the mother, except when certain conditions are met. The literature and our clinical experience have been reports linking neonatal respiratory depression with increasing temperature (37.5 ° C) and with the use of epidural fentanyl (5 mg / kg). Quality studies are needed that can rule the relationship. Meanwhile we must act prudently and take additional precautionary measures in the birth of neonatos with these risk factors.